Principlism theory in nursing practice: Resolving the autonomy-caregiver paradox - Olaolorunpo Olorunfemi; Miracle Oyindamola Olaseeni (BLDE University Journal of Health Sciences, 2025)
The ethical principle of patient autonomy is fundamental to nursing practice, promoting patient rights to make informed decisions about their care. However, this principle often conflicts with the responsibilities of caregivers to ensure patient safety and provide optimal care. Balancing these two ethical imperatives presents a significant challenge in healthcare settings, where ethical dilemmas frequently arise, impacting both patient outcomes and caregiver well-being. The purpose of this study is to thoroughly analyze how nurses balance the requirement of respecting patient autonomy with their overall responsibilities as caregivers. The terms “nursing ethics, balancing, patient, autonomy, caregiver, and responsibilities” were used to search electronic databases such as Google Scholar, CINAHL, PubMed, and MEDLINE, as well as previously examined literature containing developed theories from published studies. The literature was reviewed for eligibility, and the search year was limited to 2018–2023 to incorporate the elements identified. In the review, we found the following themes: nursing ethics, patient autonomy, caregiver responsibilities, and strategies to balance patient autonomy and caregiver responsibilities. In conclusion, balancing patient autonomy and caregiver responsibility is challenging but form important component of nursing ethics. This review highlights the importance of ongoing ethical training for nurses, supportive institutional frameworks, and patient-centered approaches to improve ethical decision-making in nursing practice. Addressing these difficulties allows healthcare practitioners to establish a more ethical and compassionate healthcare environment that respects both patient rights and caregiver duties.